Fractional CO2 Laser Treatment after Transvaginal Polypropilene Mesh for Urinary Incontinence and Pelvic Organ Prolapse Treatment as an Alternative to Improove Mesh Erosion Rates - Pablo, Gonzalez (International Journal of Innovative Research in Medical Science, 2021)
The support advantages of synthetic mesh in vaginal reconstructive surgery and stress urinary incontinence are significant. However, erosion of the mesh may occur as a complication, Four sessions of fractional CO2 Laser treatment protocol (Mona Lisa Touch Deka M.E.L.A Florence Italy protocol, were performed in the study group to 96 patients, beginning at 30 days, after mesh insertion, important improvement regarding erosion rates was found inside our study group, thanks to the trophic effects of fractional CO2 laser protocol. The use of alternative technologies that provide bio -stimulation of vaginal epithelium by increasing its thickness, and trophic changes that may be related to the very low erosion rate was found in our group of patients